Implementación de una aplicación para la sistematización de la toma de pedidos a través de tecnología android en dispositivos móviles aplicando la metodología iconix para el control de pedidos en la cocina y la generación de facturas en la hostería alma del sur en el periodo 2013 – 2014 - Simaluisa Allauca, Jenny Maribel (2016)
Nowadays, technology is changing rapidly. An example of this is the rapid migration of information from desk computers to mobile devices; there are advantages and disadvantages though. Information can be altered or the mobile devices can lose. La Hostelry Alma del Sur, in an effort to provide better service to their customers, has decided to optimize all processes of taking orders in its section of restaurant as well as the generation of automatic electronic bill. They implemented new technology and innovation. This process will help to improve customer attention so that they can gain more customers. Therefore, this research seeks systematize the process in order that the service provided can be beneficial for the Hostelry. This also will be beneficial to learn to use new technology trends such as programming mobile devices with free platforms that interact with programs in languages of new generation desktop….